Broad webbed penis with hypospadias: A rare combination (Journal of Paediatric Surgeons of Bangladesh, 2026)
Webbed penis is rare condition and may be congenital or acquired in aetiology. Treatments are indicated for reasons such as cosmetic concerns, erection pain or associated with other anomalies. We report a case of 22 years boy having broad webbed penis with penoscrotal hypospadias with severe chordee and small penis. Deformity was corrected by excision of abnormal dartos tissue attached to penis and skin between two folds for urethroplasty.Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 47-49